Second life of waste heaps - Ciesielczuk, Justyna; Fabiańska, Monika; Cygan, Weronika (No Limits, 2023)
One of the most recognisable elements of the Upper Silesian landscape is the post-mining waste heaps — remnants of coal mining — which are connected with the region’s industrial heritage that the community struggles with to this day. These sites, known to contain a mixture of toxic substances (often difficult to identify) and prone to fire, are sometimes also extremely biodiverse. Given sufficient time, the mining waste storage sites that scare away any potential passersby can turn into the so-called green islands with a spontaneously developing wildlife.